2021
DOI: 10.15252/embj.2020106536
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability by mutations in the novel minor spliceosome component CENATAC

Abstract: Aneuploidy is the leading cause of miscarriage and congenital birth defects, and a hallmark of cancer. Despite this strong association with human disease, the genetic causes of aneuploidy remain largely unknown. Through exome sequencing of patients with constitutional mosaic aneuploidy, we identified biallelic truncating mutations in CENATAC (CCDC84). We show that CENATAC is a novel component of the minor (U12-dependent) spliceosome that promotes splicing of a specific, rare minor intron subtype. This subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 97 publications
2
40
0
Order By: Relevance
“…In such cases, the outcome is typically increased minor intron retention combined with the activation of nearby cryptic U2-type splice sites. In more rare cases, splicing of the U12-type intron in question appears to be unperturbed and the splicing defect is observed only due to activation of U2-type cryptic splice sites such as those described for the SNRNPE , RCD8/EDC4 and SLC9A8 genes ( Figure 4 ; Turunen et al, 2008 ; de Wolf et al, 2021 ; Norppa and Frilander, 2021 ).…”
Section: Cooperation and Competition In Recognition Of Adjacent Splice Sites As A Means Of Regulationmentioning
confidence: 98%
See 4 more Smart Citations
“…In such cases, the outcome is typically increased minor intron retention combined with the activation of nearby cryptic U2-type splice sites. In more rare cases, splicing of the U12-type intron in question appears to be unperturbed and the splicing defect is observed only due to activation of U2-type cryptic splice sites such as those described for the SNRNPE , RCD8/EDC4 and SLC9A8 genes ( Figure 4 ; Turunen et al, 2008 ; de Wolf et al, 2021 ; Norppa and Frilander, 2021 ).…”
Section: Cooperation and Competition In Recognition Of Adjacent Splice Sites As A Means Of Regulationmentioning
confidence: 98%
“…A typical outcome in these diseases is intron retention resulting from splicing defects. However, several studies have also demonstrated that the splicing defects are not limited to U12-type introns but can also spread to the flanking U2-type introns ( Argente et al, 2014 ; Madan et al, 2015 ; Cologne et al, 2019 ; de Wolf et al, 2021 ; Olthof et al, 2021 ) in a subset of mRNAs. The most plausible explanation for these observations is that splicing of the affected U2-type introns is dependent on stabilizing exon-definition interactions with the neighboring U12-type introns ( Figure 1B ).…”
Section: Cooperation and Competition In Recognition Of Adjacent Splice Sites As A Means Of Regulationmentioning
confidence: 99%
See 3 more Smart Citations